Cum se efectueaza :
a)2√8+3√18-13√2=
b)√2(√2+√3)-√3(2√3+√2)=
c)(√5-√2)²+2√2(√5-√2)=
d)(√7+√3)(√7-√3)=
e)(3+2√2)²-(3-√8)²=
Răspunsuri la întrebare
Răspuns de
0
a)2√8+3√18-13√2=4√2+9√2-13√2=0
b)√2(√2+√3)-√3(2√3+√2)=4+√6 - 6- √6= -2
c)(√5-√2)²+2√2(√5-√2)= 5-2√10+2+10-4=13-2√10
d)(√7+√3)(√7-√3)= (√7)²-(√3)²=7-3=4
e)(3+2√2)²-(3-√8)²= 9+12√2+8 - 9+6√8-8=12√2 +12√2=24√2
b)√2(√2+√3)-√3(2√3+√2)=4+√6 - 6- √6= -2
c)(√5-√2)²+2√2(√5-√2)= 5-2√10+2+10-4=13-2√10
d)(√7+√3)(√7-√3)= (√7)²-(√3)²=7-3=4
e)(3+2√2)²-(3-√8)²= 9+12√2+8 - 9+6√8-8=12√2 +12√2=24√2
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Istorie,
9 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă